Protein enrichment of umbu-cajá residue using semisolid fermentation - Silva, Jéssica Leite da (2017)
The objective of this study was to study the protein enrichment process of the umbu-cajá bagasse with the use of Saccharomyces cerevisiae yeast by means of semi-solid fermentation. The residue was from a pulp mill located in the Pombal municipality, Paraíba state. The fermentation was carried out in bioreactors of trays placed in an air circulation oven at 37 °C for 72 hours. The highest crude protein content in the residues was 5.5% at 48 hours of fermentation. The use of yeast (Saccharomyces cerevisiae) in the semi-solid fermentation of the ubu-cajá residue makes it possible to obtain a protein concentrate, which can later be used as an alternative source of high protein potential in animal ration.